Language and culture - Kramsch, Claire J; Oxford University Press (Oxford, OX : Oxford University Press, 1998)
Several social and political changes have focused attention on the debate about the relationship between language and culture. This book offers a survey of key concepts, such as social context and cultural authenticity, using insights from fields that include linguistics, sociology and anthropology
-- The relationship of language and culture -- Meaning as sign -- Meaning as action -- Spoken language, oral culture -- Print language, literate culture -- Language and cultural identity -- Current issues
Includes bibliographical references
Keywords: Language and culture; Semantics; Sociolinguistics